Morphology and strength of acrylonitrile butadiene styrene welds performed by robotic friction stir welding - Mendes, N. (2014)
The aim of this study is to examine the main factors affecting friction stir welding (FSW) of acrylonitrile butadiene styrene (ABS) plates, performed by a robotic system developed to this purpose. Welds were carried out using a tool with stationary shoulder and an external heating system. The welding parameters studied were the axial force, rotational and traverse speeds and temperature of the tool. The major novelty is to perform FSW of a polymer in a robotic system and to study the influence of the axial force on weld quality. In a robotic solution the control of axial force allows to eliminate robot positional errors and guarantee the contact between the FSW tool and the work pieces. Strength and strain properties of the welds are evaluated and correlated with the morphology of the welded zone. A comparison between welds produced in the robotic FSW system and in a dedicated FSW machine is presented. It is shown the feasibility of robotic FSW of ABS without deteriorating the mechanical properties of the welds in relation to those produced in the dedicated FSW machine.